Farmer services: The view from above - Sibiry Traoré, Pierre C. (Technical Centre for Agricultural and Rural Cooperation, 2010)
The Seeing is Believing project uses very high resolution satellite imagery to give farmers in West Africa information on soil fertility and accurate land size.